Ab-initio evaluation of acid influence on chemical stability of hydrophilic diglycolamides - Luštinec, Jakub; Koubský, Tomáš; Kalvoda, Ladislav (Frontiers in Molecular Biosciences, 2022)
Diglycolamides (DGA) form one of the most promising groups of organic ligands used in solvent extraction processes of lanthanide and actinide ions. Continuous experimental and theoretical research is still performed in order to further improve their application properties including their chemical stability in the real extraction environment. This work provides results of our theoretical approach focused on inclusion of an acid influence on the DGAs chemical structure, treated in frame of the density functional theory. Three different models describing the acid action are proposed and investigated in attempt to increase the resulting accuracy of the chemical stability predictions based on verified theoretical descriptors. The procedure is applied and tested on the set of selected hydrophilic DGA representatives. Comparison of the model results obtained with and without acid action shows that both direct and indirect acid protection effects may occur. The possible direct acid protection is supported by the significant decrease of the Fukui charges after the acid models are included. On the other hand, there is in general no significant difference of trends in the calculated chemical stability descriptors suggesting that an indirect mechanism must be also considered in order to explain the observed protective role of acids on the chemical stability of investigated DGA derivatives.